Literature Review: The Effect of Psyllium Fiber in Type 2 Diabetic Mellitus Patient - Putu Dewinadya Saraswati (Jurnal EduHealth, 2025)
The increasing prevalence of type 2 diabetes mellitus has encouraged the search for more natural and sustainable management alternatives, one of which is through nutritional intervention using soluble fiber such as psyllium. This study aims to examine the effects of psyllium on blood glucose control and other metabolic parameters in patients with type 2 diabetes. The method used is a literature study from various relevant field studies, focusing on the results of psyllium consumption for a certain duration. The results of the study showed that psyllium was able to reduce fasting blood glucose levels, HbA1c, and increase insulin sensitivity. In addition, psyllium also contributes to weight loss and improving lipid profiles, such as reducing LDL cholesterol and increasing HDL. Thus, psyllium has great potential to be part of a comprehensive nutritional therapy that is safe and effective in managing type 2 diabetes.